Prediction of Bird Habitat Suitability: Determination and Use of Environmental Parameters - Saputra, Randi Adrian (PT. Pubsains Nur Cendekia, 2024)
A suitable habitat will support biodiversity. Knowledge of habitat suitability is essential to understanding the extent of interaction between living organisms and their environment. This study aims to analyze the determination and use of types of environmental parameters in determining the suitability of bird habitat in an area. The type of research in this study is qualitative research sourced from literature studies using the Content Analysis method. The data used in this research is secondary data sourced from reading relevant literature in scientific journal articles. The results of this study found that the most influential parameters in determining bird habitat suitability are altitude, slope, vegetation density (NDVI), and distance from water sources. This is related to the comfort and safety of birds from predators, changes in environmental conditions, and poaching that threaten the extinction of the species.